Organoselenium-Catalyzed Polymerization of Aniline with Hydrogen Peroxide as Oxidant - Gao, Ge; Han, Jie; Yu, Lei; Xu, Qing (Synlett, 2019)
A convenient method for the synthesis of polyanilines was developed through the organoselenium-catalyzed oxidation of anilines with H2O2. Unlike reported methods, this reaction generates no wastes other than water. These green features make the method much more practical in terms of large-scale preparation. Moreover, it is the first example of an application of organoselenium catalysis techniques in aniline polymerization reactions and might be an important advance in the fields of both organoselenium catalysis and polyanilines.
Keywords: selenium catalysis; organoselenium compounds; green chemistry; aniline; polymerization; polyaniline